Blog jornalístico: a constituição do sujeito jornalista-blogueiro e do leitor digital - Andrade, Alaíse Maria Carrijo Ramos e (2008)
This dissertation presents a analysis of two journalistic weblogs Verbo Solto by Luis Weis and Nos bastidores do poder by Josias Souza. The main aim was to reflect upon the discourse, identitary and reading practices found in the mentioned weblogs. In order to do so, we verified which discourse and reading practices are present and which identities the readers and authors assume in this text support during this interlocution process. We also analyze the power relations and the discourse order present in the blogs. Considering the web as a “new” type of media and the journalistic blogs as one of its mechanisms, our hypothesis is that there should be a new journalistic subject and a new journalistic reader different from the ones found in traditional media and who re(define) more freeing discourse, identitary and reading relations. The importance of this work relies on the fact that there are a few studies about the journalistic blogs. Our theoretical basis is the Discourse Analysis of the French school, whose founding scholar was Michel Pêcheux who considers the discourse subject in constant process of construction regarding social, historical and ideological factors. Besides Pêcheux, Foucault and other authors in the area of discourse and social science, our work has consider theoretical principles developed by scholars who research about post-modernity, Lévy, Bauman and Baudrillard; blogs, Orihuela, Lemos and Schittine; communication theory, Castells and Barbosa and Granado; and reading practices, Chartier. The results have indicated that the new technologies at exam did not determine new identities, but different forms of identification of the post-modern subject.